Dissolução da adoção: um estudo sobre a devolução de crianças e adolescentes - Magalhaes, Luisa Taveira (2022)
Adoption in Brazil is governed by the Child and Adolescent Statute and the National Adoption Law. In view of this legislation, adoption is understood as an exceptional and irrevocable act, in addition, research data already show increasing numbers of children and adolescents returning to foster care after approval of approval, a phenomenon named in this work as dissolution of promotion. Thus, this dissertation, divided into two complementary articles, presents data on the issue of dissolution of adoption in the state of Rio Grande do Sul. In the first, the occurrence of the phenomenon in the state between the years 2018 and 2020 was mapped through of document analysis. The data provided by the Coordination of Childhood and Youth of RS, referred to a total of eight processes that took place in the last three years. Through descriptive analysis, the results dissipated that the time from adoption to dissolution ranged from 30 to 2920 days, with the lack of attachment being the main motivator for the return to reception. In addition, it was identified that entering adolescence can be a risk factor for dissolution of adoption, a period that was in seven of the eight cases studied. Finally, the data reflected non-compliance with legislation in different spheres of the adoption process. In the second article, through a case study, an attempt was made to understand systemically, from different perspectives (professionals, adopters and adopted), how the process of dissolution of adoption was experienced. A mother by adoption, the adolescent who was adopted and returned to foster care, and the team from the foster care home (psychologist, social worker and educators) who monitor the case participated. The instruments used were the genogram, the family design and semi-structured alterations. The data were triangulated and the results pointed to non-compliance with what is provided for by law, lack of identification of the risk situation and post-adoption follow-up, in addition to the search for blame among those involved. It is concluded that the hypotheses of dissolution experienced in practice alert to the need to intensify post-adoption follow-up and questions regarding the legislation.